Kewajiban Seorang Anak dalam Menghormati Orang Tua Ditinjau dari Efesus 6:2 - Holong P Simamora; Faogosokhi Ndruru (Sekolah Tinggi Teologi Paulus Medan, Sumatra Utara, 2023)
The research aims to show a child's obligation to respect their parents according to Ephesians 6: 2. This research is based on the argument that parents are God's representatives towards their children regarding His authority and His love. This research shows that when children respect their parents, it means they heed and acknowledge the authority that God has given to their parents, and the child is obliged not only to obey but also love and respect their parents. So because the authority of parents over children is God's authority that God delegated to them, then in the life of the Israelites who received God's promises, children's obedience to parents was given such importance as is seen in the Bible. This research uses the exegesis method to produce interpretations and construct them in the form of principles of children's obligations to their parents.